The renovation of the taxonomic classification of the Order Chlamydiales microorganisms - Zezekalo , V. K.; Peredera , S. B.; Shcherbakova , N. S. (Scientific Progress & Innovations, 2019)
The purpose of the article is to provide the currently relevant taxonomic classification of the Order Chlamydiales, and give a detailed explanation of the terms: “Chlamydia-related bacteria (CRB)”, “Chlamydia-like organisms (CLO)”, "Environmental chlamydiae" (ecological chlamidiae). Research methods. The following research methods were used: system analysis of the available scientific sources, historical method (to study the origin, formation and development of the taxonomy of chlamydia species in chronological order), empirical method (concerning the comlex assessment of the current state of the research object), abstract-logical – to clarify the essence of the basic notions and graphical reflection of the data. The results of the study. As a result of molecular biology development during the recent 15 years, the classification of chlamydia has undergone significant changes and has the tendency to further improvement. This review article is aimed at summarizing the historical experience and the most important changes in the taxonomy of the Order Chlamydiales in recent years. The complication of the modern classification of the Order Chlamydiales bacteria is the inevitable consequence of accumulating knowledge about the new representatives of this group of microorganisms. Consequently at present there are 9 families in the Order Chlamydiales: Chlamydiaceae, Waddliaceae, Parachlamydiaceae, Criblamydiaceae, Simkaniaceae, Candidatus Clavochlamydiaceae, Candidatus Rhabdochlamydiaceae, Candidatus Piscichlamydia, Candidatus Parilichlamydiaceae, four of them are in the status of candidates. Currently, 14 species of bacteria belong to the family Chlamydiaceae, the genus Chlamydia (Chlamydia abortus, Chlamydia avium, Chlamydia caviae, Chlamydia felis, Chlamydia gallinacea, Chlamydia muridarum, Chlamydia pecorum, Chlamydia pneumoniae, Chlamydia psittaci, Chlamydia suis, Chlamydia trachomatis, Candidatus Chlamydia ibidis, Candidatus Chlamydia sanzinia, Candidatus Chlamydia corallus), three of which are the candidates. Such families as: Waddliaceae, Parachlamydiaceae, Criblamydiaceae, Simkaniaceae, Ca. Clavochlamydiaceae, Ca. Rhabdochlamydiaceae, Ca. Piscichlamydia, Ca. Parilichlamydiaceae with their numerous representatives are called Сhlamydia-related bacteria, or Сhlamydia-like organisms, due to their genetic and phenotypic similarity, and phylogenetic isolation from the Chlamydiaceae family. The elements of scientific novelty. The currently relevant taxonomic classification of Chlamydiales is presented in the article and also given a detailed explanation of the terms: “Chlamydia-related bacteria (CRB)”, “Chlamydia-like organisms (CLO)”, "Environmental chlamydiae". Practical significance. The provided information can be used in scientific research, introduced into the educational process for training specialists of veterinary medicine, and also be used by practicing veterinary doctors in order to improve the treatment and prevention of animals and human chlamydioses.